Developing Google Sites-Based Learning Media for Grade 8 Informatics Instruction - Nada Safarina; Gusnita Darmawati; Firdaus Annas; Yulifda Elin Yuspita (Yayasan Lembaga Studi Makwa, 2026)
Teachers tended to rely on lecture-based instruction and used only the whiteboard and textbooks when explaining the material. As a result, student interaction was limited and conceptual understanding, particularly in Informatics, remained low, which reduced students’ engagement in the learning process. This study aimed to develop Google Sites-based learning media for Grade 8 Informatics instruction at SMP Negeri 5 Padang Panjang. The study employed a Research and Development (R&D) approach using the 4D model, which consists of the stages of Define, Design, Develop, and Disseminate. The developed media were evaluated through product testing using Aiken’s V for validity, Moment Kappa for practicality, and Hake’s G-Score for effectiveness. The results showed that the Google Sites-based learning media achieved an average validity score of 0.84, indicating that it was valid. The practicality test produced an average score of 0.92, which was categorized as very high, while the effectiveness test involving 27 students resulted in an average score of 0.87, also in the very high category. This study contributes by providing Google Sites-based learning media that are valid, practical, and effective, offering an alternative solution for teachers to implement more interactive and efficient learning while supporting students’ motivation. Abstrak Guru cenderung menggunakan metode ceramah serta hanya memanfaatkan papan tulis dan buku dalam menjelaskan materi. Akibatnya, interaksi siswa masih terbatas dan pemahaman konsep, terutama pada mata pelajaran Informatika, masih rendah sehingga keterlibatan siswa dalam proses pembelajaran belum optimal. Penelitian ini bertujuan untuk mengembangkan media pembelajaran berbasis Google Sites pada mata pelajaran Informatika kelas VIII di SMP Negeri 5 Padang Panjang. Penelitian ini menggunakan pendekatan Research and Development (R&D) dengan model 4D yang terdiri atas tahap Define, Design, Develop, dan Disseminate. Media yang dikembangkan dievaluasi melalui uji produk menggunakan Aiken’s V untuk validitas, Moment Kappa untuk praktikalitas, dan Hake’s G-Score untuk efektivitas. Hasil penelitian menunjukkan bahwa media pembelajaran berbasis Google Sites memperoleh skor validitas rata-rata 0,84 dengan kriteria valid. Uji praktikalitas memperoleh skor rata-rata 0,92 dengan kriteria sangat tinggi, sedangkan uji efektivitas yang melibatkan 27 siswa menghasilkan skor rata-rata 0,87 dengan kriteria sangat tinggi. Penelitian ini berkontribusi dengan menghadirkan media pembelajaran berbasis Google Sites yang valid, praktis, dan efektif sebagai alternatif bagi guru untuk melaksanakan pembelajaran yang lebih interaktif dan efisien serta mendukung motivasi siswa.